Effects of CLIL on second language learning: Disentangling selection, preparation, and CLIL-effects. (August 2021) - Feddermann, Maja; Möller, Jens; Baumert, Jürgen
Abstract: The positive effects of Content and Language Integrated Learning (CLIL) on the development of students' foreign language skills may have been overestimated by previous studies, since most studies failed to consider selection and preparation effects appropriately. Therefore, the present study used complete survey data from a 2002–2007 cohort to investigate English skill development of N = 385 German CLIL and N = 5, 578 non-CLIL grammar school students from grade seven ( M = 12.46, SD = 0.53) to grade eight ( M = 14.46, SD = 0.53). Firstly, we found significant selection effects for performance in primary school, sociodemographic variables, and cognitive abilities. Secondly, after propensity score matching, data revealed significant preparation effects of additional second language instruction for the CLIL students. When controlling selection and preparation effects, only a small and non-significant CLIL effect occurred measured by a C-test. We discuss the results with regard to previous inconsistent findings. Highlights: Consideration and estimation of selection, preparation, and CLIL-effects. Significant selection and preparation effects. Small positive non-significant CLIL effect. Use of full survey data and a large sample size. Conduction of a Propensity Score Matching.